A Study On The Expressions Of Politeness In Senior High School English Textbooks - Rohim, Abdul, Drs. Agus Wijayanto M.A., Ph.D, Dr. Anam Sutopo, M.Hum (2015)
Politeness occupies a very important aspect for students in having communications. It appears in the characteristic instruction in The School Based Curriculm or KTSP, and the Main Competence 2 in Curriculum 2013 which obligates teachers to teach their students to perceive and accomplish politeness in communication. The writer does a research on the uses of politeness through Real English for Senior High School Textbooks Grade X, XI and XII by Erlangga publisher to describe about what characteristics of expressions of politeness are included the textbooks in the forms of ; (1) texts, (2) explanations and (3) exercises. The research is based on the Politeness Strategies proposed by Brown and Levinson which the Politeness Strategies here include; bald on record, positive, negative, and off record indirect politeness strategy. The writer uses a descriptive qualitative research to do the research in which the writer searches, collects, classifies, analyzes data, and then draws the conclusion. The data are the utterances expressed by the characters in the textbooks containing the politeness expressions. The collected data then analyzed on the theory of Politeness Strategies proposed by Brown and Levinson. The ending of the analysis is the conclusion of the result of data. The result of the research shows that in the forms of texts, Book X, XI and XII have 88 utterances of bald on record, 223 positive, 136 negative and 49 off record politeness strategies, with the total sum of 496 politeness strategies. In the forms of explanations, the books provide 3 explanations of bald on record, and 7 positive politeness strategies. In the forms of exercises, they have 10 expressions of bald on record, 7 positive, 2 negative and 2 off record politeness strategies with the total number of 21 politeness strategies. The total sums of the politeness strategies are 101 bald on record or 19%, 237 positive or 45%, 138 negative or 26%, and 51 off- record or 10% with the total number of 572 politeness strategies. The finding of the research shows that the characters in the books use all the four politeness strategies in their utterances with 3 data of the expressions which are considered as being impolite as they are in contrast against the politeness strategy to give a gift to H.